2019
DOI: 10.1186/s12894-019-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

RRM1 predicts clinical outcome of high-and intermediate-risk non-muscle-invasive bladder cancer patients treated with intravesical gemcitabine monotherapy

Abstract: Background The expression level of ribonucleotide reductase subunit M1 (RRM1) is closely related to the effect of gemcitabine-based therapy in advanced bladder cancer. However, the value of RRM1 expression in predicting progression-free survival in non-muscle-invasive bladder cancer (NMIBC) patients treated with intravesical gemcitabine chemotherapy has not been elucidated. Methods This study randomly assigned 162 patients to either the RRM1-known group or the unknown g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…RRM1 could regulate metabolization and activity of mitotane 23 . Previous research has demonstrated that higher RRM1 expression is discovered to associated with shorter overall survival in non‐small cell lung cancer (NSCLC), 24 non‐muscle‐invasive bladder cancer (NMIBC) 25 and multiple myeloma patients 26 . UCK2 could convert uridine and cytidine to uridine monophosphate (UMP) and cytidine monophosphate (CMP), promoting metastasis of HCC cells via the STAT3/MMP2/MMP9 signal axis 27 .…”
Section: Discussionmentioning
confidence: 99%
“…RRM1 could regulate metabolization and activity of mitotane 23 . Previous research has demonstrated that higher RRM1 expression is discovered to associated with shorter overall survival in non‐small cell lung cancer (NSCLC), 24 non‐muscle‐invasive bladder cancer (NMIBC) 25 and multiple myeloma patients 26 . UCK2 could convert uridine and cytidine to uridine monophosphate (UMP) and cytidine monophosphate (CMP), promoting metastasis of HCC cells via the STAT3/MMP2/MMP9 signal axis 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, these polymorphisms have been associated with different cancers and other complex diseases. The RRM1 gene, for example, has been related to a high degree of sensitivity to oncological chemotherapy (Yang et al, 2019 ; Zhao et al, 2012 ) and has been identified as a predictive factor in gemcitabine therapy in oncology patients (Jordheim et al, 2011 ). The ABCG2 gene has also been associated with resistance to chemotherapy in the treatment of many types of cancer (Amawi et al, 2019 ; Robey et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not use any stratification of risk by using biomarkers or molecular characterization 28 . Yang et al investigated the predictive role of Ribonucleotide reductase subunit M1 (RRM1) mRNA in patients who received gemcitabine 29 . A total of 1000 mg of gemcitabine was diluted in 40 mL of saline solution, and patients received weekly instillations for eight consecutive weeks and once a month for 1 year.…”
Section: Discussionmentioning
confidence: 99%